ANALISIS KELAYAKAN USAHA TERASI UDANG REBON DI KELOMPOK PENGOLAH DAN PEMASAR (POKLAHSAR) SETYA BAKTI DESA SIRNOBOYO KECAMATAN PACITAN KABUPATEN PACITAN - Nugraha, Jefri Putri; Mareta, Zayafika; Suseno, Dewi Alima Nostalia; Waluyo, Buyung Purnomo (Politeknik Kelautan dan Perikanan Sidoarjo, 2022)
The processing of rebon shrimp paste has been widely carried out by people in the coastal area of Pacitan as a side activity in increasing family economic income and also participating in national development efforts in the fisheries sector. This study aims to measure the feasibility of rebon shrimp paste processing business based on financial (financial) aspects. This research was conducted during September 2022, in Sirnoboyo Village, Pacitan District, Pacitan Regency, East Java. This study uses a quantitative descriptive research method. Descriptive quantitative research method is a method that aims to make pictures or descriptive of a situation objectively using numbers, starting from data collection, interpretation of the data and appearance and results. Sampling of the research was carried out on rebon shrimp shrimp paste entrepreneurs, members of Poklahsar Setya Bakti in Sirnoboyo Village. The feasibility of a business from the financial aspect is measured using the analysis of discounted investment criteria, namely the net present value, the rate of return on investment capital (internal rate of return), the ratio of net benefits to costs (net benefit cost ratio), investment return period (payback period). The shrimp paste processing business carried out by members of Poklahsar Setya Bakti in Sirnoboyo Village has good prospects for development in the future. This business is financially feasible with NPV = Rp. 32,667,112,-. IRR = 21%, Net B/C = 2.1 and a payback period of 3.3 years.